A study of prevalence and risk factors of overweight in lower secondary school students in Kota Bharu District, Kelantan. - Mustaffa, Ruzita (2001)
A cross-sectional study involving 392 subjects was conducted from June to November 2000 to detennine the prevalence of overweight and associated risk factors in 14 years old school students in Kota Sharu District Two schools, Sekolah Menengah Ketereh and Sekolah Menengah Kok Lanas were selected for the study involving students in form two. Family history, sociodemographic factors, dietary practices, physical activity pattern, and body mass index 'Nere assessed using structured self-administered questionnaire and anthropometric measurements. Overweight was defined as body mass index-far-age and sexequal or greater than 85th percentile (BMJ-for-age and sex > 85th percentile). The prevalence of overweight was found to be 17.3%. The prevalence rate was 18.2% and 16.4% in males and females, respectively. There was no significant difference across schools. gender and ethnicity. Factors contributing toward increased risk for overweight include those who have a family history of overweight {OR 2.1; 95% CI:1.0-3.8}, skipped breakfast (OR 9.6; 95% CI:3.5- 13.6), 2 hours or more viewing television daily (OR 3.0 ; 950/0 CI:1.D-4.0), misperception of bodyweight (OR 6.4; 95% CI:3.0-11.4) and physical activities less than 3 times per week (OR 2.8; 950/0 CI:1.4-S.4). Whilst the problem may not be as serious as that in developed countries, the findings of this study should serve as an earty warning to health authorities of the seriousness of the problem. With this information, some measures can be taken to enable adolescents to adopt healthier eating habits, perceived self-bodyweight correctly, fewer hours of viewing television and increased physical activity pattern to reduce or avoid risk factors of overweight